Meningkatkan Prestasi Belajar Siswa Kelas XI SMP pada Materi Pangkat dan Akar Menggunakan Metode Diskusi - Rahman Rahman (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
The purpose of this study is to find out whether the use of discussion methods in the Rank and Root material can improve the learning achievement of students in class IX 2 in Pujut 1 Public Middle School. The type of research used in this study is Classroom Action Research. Data collection in the form of observation sheets, critical thinking tests and cognitive learning outcomes. In the first cycle, the average student achievement was 63.92 and in the first cycle, there were 12 students (48%), 13 students were incomplete (52%). In the second cycle, the average student achievement was 82.04 and in the third cycle there were 22 students (88%), 3 students were not complete (12%). It was concluded that there was an increase in student achievement from the first cycle to the second cycle. Thus the discussion method can improve the learning achievement of class IX 2 students on the subject matter and roots.